Bioactivity of medicinal plants used for treatment of diarrhoea in selected villages in Limpopo Province, South Africa - Mathabe, Matlakala Christina (University of Limpopo (Turfloop Campus), 2006)
Refer to document
Thesis (Ph.D (Plant Physiology) --University of Limpopo, 2006
Keywords: Medicinal plants; Diarrhoea; 581.634; Botany, Medical -- South Africa; Medicinal plants -- South Africa